Rethinking the good moral ideals and the nature of practical reasoning - Temkin, Larry S. (New York ; Oxford : Oxford University Press, 2012)
In choosing between moral alternatives we typically make calculations of the following kind, using the principle of transitivity: A is better than B; B is better than C; therefore A is better than C. Temkin shows that if we want to continue making plausible judgments, we cannot continue to make these assumptions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Good and evil; Practical reason